1991
DOI: 10.1088/0953-8984/3/27/009
|View full text |Cite
|
Sign up to set email alerts
|

Order parameter coupling and chirality of domain walls

Abstract: Biquadratic coupling between W O order parameters Q , and Q2 can lead to transitionsbetweenaphase withonlyoneof thehvoorderparametersactive(phase1orII) andamivedphaseIIIinwhich bothorderparametenaresymmetry breaking. Domain walls for positive coupling energies are chiral under thermodynamic conditions close to the transition points 1-111 and 11-111. Annihilation of chirality in the wall leads to wall widening and wall bifurcations. The widths of the walls are different for the hvo order parameters leading to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
135
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 11 publications
9
135
1
1
Order By: Relevance
“…In terms of structural depiction, the two dipoles of AFE materials are described generally by two different order parameters, P and η. Consequently, as a result of temperature induced phase transitions and symmetry breaking, the pairing that occurs between these structural order parameters can lead to the phase transition with only one of the them active [7]. These structural changes can in principle lead to most of the important physical properties such as FE occurring in AFE materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of structural depiction, the two dipoles of AFE materials are described generally by two different order parameters, P and η. Consequently, as a result of temperature induced phase transitions and symmetry breaking, the pairing that occurs between these structural order parameters can lead to the phase transition with only one of the them active [7]. These structural changes can in principle lead to most of the important physical properties such as FE occurring in AFE materials.…”
Section: Introductionmentioning
confidence: 99%
“…These structural changes can in principle lead to most of the important physical properties such as FE occurring in AFE materials. For example, it is interesting to learn how the local order parameters near domain walls react to the structural coupling phenomena [7]. It was hypothesized by these authors [7] that because of order parameter coupling inside the AFE domain wall, in regions where the local order parameter (η) becomes zero; FE can be favored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…general symmetry-allowed term that describes competition between two order parameters 5 ; the trilinear coupling leads to improper ferroelectrics 40 ; and the flexoelectric coupling produces incommensurate domain patterns 41 . However, the relative contributions of these coupling to the structures and properties of domain walls remain unclear.…”
mentioning
confidence: 99%
“…In addition to the x 2 direction polarization, it is shown that there exists additional antiferroelectric (AFE)-like polarization distribution along x 1 direction by the molecular dynamics 14 , firstprinciples calculations 12 and the LGD theory 4 . Such a complicated polarization configuration inside the twin wall has been attributed to the improper AFD-AFE coupling 12 , flexoelectric coupling 4 , or the biquadratic coupling 5 by different research groups. In this work, we first employ the LGD theory in combination with phase-field method to elucidate the underlying thermodynamic driving forces leading to the formation of polar domain walls in CaTiO 3 .…”
mentioning
confidence: 99%